An Investigation of Selective Catalytic Reduction Catalyst SO2/SO3 Conversion in Coal-fired Power Plants - Yang Zhang; Zhiqiang Jiang; Zhengang Zhou; Yonglong Yang; Qianwei Feng; Jianping Jiang; Zhen Du; Dong Guo; Xinrong Yan (Aerosol and Air Quality Research)
Abstract The SO2/SO3 conversion in the selective catalytic reduction (SCR) denitrification system of coal-fired power plants plays a significant role in the generation of SO3. Effectively controlling the conversion rate of SO2/SO3 in the denitrification catalyst can substantially mitigate the hazards associated with SO3. Drawing on 170 SCR catalyst tests, the impact of various factors, including the catalyst’s V2O5 content, WO3/MoO3 content, inlet SO2 concentration, inlet flue gas temperature, and area velocity, on the SO2/SO3 conversion was systematically investigated. The findings suggest potential optimization opportunities for the SO2/SO3 conversion rate in the denitrification catalysts currently used in engineering applications. By understanding the influence patterns of key factors, tailored measures such as selecting appropriate performance indicators, designing catalysts for specific projects, and adjusting key operational parameters in coal-fired power plants can be implemented. These measures are aimed at preventing problems like corrosion and blockage in downstream facilities due to SO3 and effectively controlling SO3 emissions.